(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
ABSTRACT Medical science is constantly searching for bioactive compounds derived from sustainable natural sources with therapeutic and preventive impact. The main goal of this article is to shine a light on the biological activities of fig (Ficus carica L.) extract and latex, as most studies focused on the health benefits of fig fruits. This work also aims to identify the potential of fig (either extracts or latex) in the treatment or prevention of various diseases. Especially since fig latex or extract has numerous biological activities, such as antidiabetic, antioxidant, and anticancer properties.